Truth Default or Generalized Skepticism? The Role of Overconfidence in the Relationship Between Social Media News Use and Traditional Media Use - Taewoo Kang; Kjerstin Thorson; Chankyung Pak (Social Media + Society)
This article examines a model positing that overconfidence in political understanding resulting from social media use for news and politics hampers traditional media use. It confirms a positive relationship between Facebook political information experiences and overconfidence in political understanding. However, contrary to expectations, there is a positive relationship between overconfidence and traditional media use. An exploratory post hoc analysis, viewed through the lens of truth vs. false-default orientations, suggests overconfident users might use traditional news outlets to confirm their sense of knowledge, thereby exhibiting a false-default orientation on social media political information.